Beginning shell scripting - Foster-Johnson, Eric (Programmer to programmer., 2005)
Overing all major platforms-Linux, Unix, Mac OS X, and Windows-this guide shows programmers and power users how to customize an operating system, automate commands, and simplify administration tasks using shell scripts.